Seroadaptive Strategies of Gay & Bisexual Men (GBM) With the Highest Quartile Number of Sexual Partners in Vancouver, Canada - Card, Kiffer G. (AIDS Behav, 2017)
Despite continued research among men with more sexual partners, little information exists on their seroadaptive behavior. Therefore, we examined seroadaptive anal sex strategies among 719 Vancouver gay and bisexual men (GBM) recruited using respondent driven sampling (RDS). Our objectives were to (1) describe the distribution in frequency of male sexual partnering among Vancouver GBM, and (2) identify important covariates associated with the number of male sexual partners. To this aims, we provide descriptive, univariate, and multivariate adjusted statistics, stratified by HIV status, for the association between having ≥7 male anal sex partners in the past six months (Population Q3, versus <7). Sensitivity Analysis were also performed to assess the robustness of this cut-off point. Results suggest that GBM with more sexual partners are more likely to employ seroadaptive strategies than men with fewer partners. These strategies may be used in hopes of offsetting risk, assessing needs for subsequent HIV testing, and balancing personal health with sexual intimacy. Further research is needed to determine the efficacy of these strategies, assess how GBM perceive their efficacy, and understand the social and health impacts of their widespread uptake.